2008
DOI: 10.2337/dc08-0513
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hyperglycemic Dysregulation in Patients With Type 1 Diabetes Does Not Change Myocardial Triglyceride Content or Myocardial Function

Abstract: OBJECTIVE -To evaluate the effects of hyperglycemia due to partial insulin deprivation on myocardial triglyceride (TG) content and myocardial function in patients with type 1 diabetes.RESEARCH DESIGN AND METHODS -Myocardial and hepatic TG content and left ventricular (LV) function were measured by magnetic resonance (MR) spectroscopy and MR imaging during optimal glucoregulation and after 24 h of partial insulin deprivation (n ϭ 10).RESULTS -Mean insulin infusion rate was 45 Ϯ 5 units at baseline, whereas it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Similarly, in fasting conditions, glycogen depots tended to be lower and RPP was higher. In line with our findings, elevations in HR and RPP have been observed in patients with type 2 diabetes or those fed a high-fat diet [1,16] while no change in haemodynamic variables has been observed following an acute exposure to isolated hyperglycaemia [38] or combined hyperinsulinaemiahyperglycaemia [34].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, in fasting conditions, glycogen depots tended to be lower and RPP was higher. In line with our findings, elevations in HR and RPP have been observed in patients with type 2 diabetes or those fed a high-fat diet [1,16] while no change in haemodynamic variables has been observed following an acute exposure to isolated hyperglycaemia [38] or combined hyperinsulinaemiahyperglycaemia [34].…”
Section: Discussionsupporting
confidence: 78%
“…However, the increase in myocardial GU did not translate into a significant elevation in myocardial TG accumulation compared with that of the hyperinsulinaemic state alone. Hammer et al [38] reported that 24 h of hyperglycaemia achieved by partial insulin deprivation in patients with type 1 diabetes did not affect the myocardial TG content. In contrast, Winhofer et al [34] demonstrated that combined hyperglycaemia and hyperinsulinaemia induced myocardial lipid accumulation in normal individuals, independent of insulin resistance and while plasma NEFA were suppressed; the authors suggested that insulinaemia rather than glycaemia was responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Our data is in line with previous publications of a large cohort of patients with T1DM participating in the diabetes control and complications trial (DCCT), in which cardiac geometry and function was normal 33 . Also, short-term hyperglycemic dysregulation after partial insulin deprivation for 24 hours had no effect on MYCL 34 . Thus, MYCL adapts differently in T1DM compared to insulin sensitive, healthy subjects, in which even in the absence of circulating free fatty acids an elevation in glucose concentrations significantly increased lipid deposition within the myocardium 24 .…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that this risk was minimized by patients giving themselves larger boluses of insulin following meals, which we had to allow for safety. Recently though, short term glycemic dysregulation in patients with type 1 diabetes has been shown not to modulate cardiac function(29) which is compatible with no significant rise in markers of oxidative stress with short term hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%